2012
DOI: 10.1123/ijspp.7.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Bicarbonate on Performance and Hydration in Lightweight Rowing

Abstract: Purpose:The effect of sodium bicarbonate (NaHCO3) ingestion on prerace hydration status and on 2000 m ergometer performance in elite lightweight rowers was examined using a randomized, cross-over, double-blinded design.Methods:To simulate body mass (BM) management strategies common to lightweight rowing, oarsmen reduced BM by approx. 4% in the 24 h preceding the trials, and, in the 2 h before performance, undertook nutritional recovery consisting of mean 43.2 kJ/kg, 2.2 g of CHO per kilogram, 31.8 mg of Na+ pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Alternatively, the higher post-exercise blood [La -] in BIC might be due to reduced Laclearance, as it was reported that Laclearance by inactive skeletal muscle tissue is reduced following NaHCO 3 supplementation [22]. In contrast to Δ[HCO 3 -] and Δ[La -], the exercise-induced drop in blood pH was similar between BIC and PL, despite higher pre-exercise pH values in BIC, which is in agreement with other studies [23][24][25]. The similar drop in pH during exercise in both conditions seems counterintuitive.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, the higher post-exercise blood [La -] in BIC might be due to reduced Laclearance, as it was reported that Laclearance by inactive skeletal muscle tissue is reduced following NaHCO 3 supplementation [22]. In contrast to Δ[HCO 3 -] and Δ[La -], the exercise-induced drop in blood pH was similar between BIC and PL, despite higher pre-exercise pH values in BIC, which is in agreement with other studies [23][24][25]. The similar drop in pH during exercise in both conditions seems counterintuitive.…”
Section: Discussionsupporting
confidence: 90%
“…Despite significant elevation of blood and pH before exercise and blood lactate immediately following exercise, we failed to detect a clear performance benefit of NaHCO 3 loading on a 4-km cycling TT (~5.5 min). Indeed, this is similar to findings from other studies involving exercise protocols of similar duration (Carr et al, 2011c;Christensen et al, 2014;Kupcis et al, 2012) and again demonstrates that certain conditions such as high intensity short-duration (~1-min) events involving repeated efforts may be needed before clear benefits are seen (Sutton et al, 1981). Although benefits provided by NaHCO 3 loading may be counteracted by the potentially associated gastrointestinal distress, this risk can be reduced by the use of specific protocols involving encapsulated supplements, a spread intake, and coingestion with a light carbohydrate meal (Carr et al, 2011b).…”
Section: Discussionsupporting
confidence: 80%
“…ammonium chloride (NH 4 Cl)) to determine the wider contribution of acid-base perturbation on skeletal muscle fatigue; however, emphasis has been placed on reviewing only the alkalosis condition in most instances. This review does not address all performance-based applications of NaHCO 3 supplementation in the literature, such as team sport performance [ 15 17 ], skill sports [ 18 20 ], hydration [ 21 , 22 ] or the efficacy of NaHCO 3 under hypoxic conditions [ 23 25 ].…”
Section: Reviewmentioning
confidence: 99%